Rosemary and Sage Outperformed Six other Culinary Herbs in Antioxidant and Antibacterial Properties - Chan, Eric W.C.; Kong, Lei Quan; Yee, Kar Yen; Chua, Wen Yee; Loo, Tze Ying (International Journal of Biotechnology for Wellness Industries, 2012)
The antioxidant and antibacterial properties of Labiatae culinary herbs are well documented but the effects of different drying methods are poorly studied. In this study, the antioxidant and antibacterial properties of fresh and oven-dried herbs of oregano, marjoram, rosemary, sage, basil, thyme, peppermint and spearmint were compared with available commercial herbs. Antioxidant properties of total phenolic content, total flavonoid content, caffeoylquinic acid content, free radical scavenging activity, ferric reducing power and ferrous ion chelating ability were assessed using the Folin-Ciocalteu, aluminium chloride, molybdate, DPPH radical scavenging, potassium ferricyanide and ferrozine assays, respectively. Antibacterial properties were assessed using the disc diffusion assay based on mean diameter of inhibitory zone and minimum inhibitory dose. The two drying treatments were oven drying at 50oC (OD) and microwave pre-treatment followed by oven drying at 50oC (MOD). Fresh rosemary and oven-dried oregano had the strongest antioxidant properties. For most herbs, oven drying resulted in loss of antioxidant values compared to fresh herbs with the exception of oregano. Values of oven-dried oregano, spearmint, thyme, peppermint and basil were higher than commercial samples, while those of oven-dried rosemary were lower. Of the six commercial herbs, rosemary had the highest values, followed by oregano, spearmint, thyme, peppermint and basil. All herbs showed no antibacterial activity against Gram-negative Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi. Rosemary, sage, peppermint and spearmint inhibited the growth of Gram-positive Bacillus cereus, Micrococcus luteus and Staphylococcus aureus. Rosemary and sage had stronger antibacterial properties than green and black teas of Camellia sinensis. When used in combination, rosemary and sage can have enhanced antioxidant and antibacterial effects, which are desirable in developing nutraceutical products, and in controlling rancidity and bacterial growth in food.